Low-cost tools for diagnosing and monitoring HIV infection in low-resource settings - Grace Wu; Muhammad H Zaman (The World Health Organization, 2012)
Low-cost technologies to diagnose and monitor human immunodeficiency virus (HIV) infection in developing countries are a major subject of current research and health care in the developing world. With the great need to increase access to affordable HIV monitoring services in rural areas of developing countries, much work has been focus on the development of point-of-care technologies that are affordable, robust, easy to use, portable and of sufficient quantitative accuracy to enable clinical decision-making. For diagnosis of HIV infection, some low-cost tests, such as lateral flow tests and enzyme-linked immunosorbent assays, are already in place and well established. However, portable quantitative tests for rapid HIV monitoring at the point of care have only recently been introduced to the market. In this review, we discuss low-cost tests for HIV diagnosis and monitoring in low-resource settings, including promising technologies for use at the point of care, that are available or close to market.